Underplanting in Teak Plantations in Madras State - Venkataramany, P. (Indian Forester, 1956)
The term underplanting is defined and explained. Theoretically a high forest with an under crop produces greater volume yield than pure stands; but in practice such stands are unknown in India or abroad. The advantages of a two storeyed high forest, resulting from underplanting are enumerated and their application to Indian conditions discussed. Underplanting pure Teak plantations is not necessary in Madras State as there is a considerable amount of under growth to protect the soil and also as per measurements in S.Ps. 17A, 18A, 19A of Nilambur, in 1955, there is no deterioration of site quality of a pure teak plantation even in the second rotation. But in 1928, there was a genuine apprehension that a pure teak plantation cannot adequately protect the soil from the adverse effects of exposure, desiccation and erosion and hence experiments in underplanting were started in Madras in 1928.